2007
DOI: 10.1523/jneurosci.1249-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical and Physiological Evidence for Parallel Afferent Pathways Mediating the Sensation of Itch

Abstract: The neuronal pathways for itch have been characterized mainly based on responses to histamine. Intracutaneous application of histamine produces intense itch and a large area of axon-reflexive vasodilation ("flare") around the application site. Both phenomena are thought to be mediated through neuronal activity in itch-specific, mechanoinsensitive C-fiber afferents (CMi). However, mechanical and electrical stimuli that do not activate CMi fibers can cause the sensation of itch, and itch may occur without flare,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
156
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 32 publications
19
156
1
3
Order By: Relevance
“…The existence of multiple subsets of neurons responding to itch-provoking stimuli is supported by recent reports that histamine-and cowhage-induced itch involve different sensory circuits (26)(27)(28)(29). Histamine-induced calcium responses were observed in 23% of IB ϩ and 7% of the IB4 Ϫ neurons (9).…”
mentioning
confidence: 61%
“…The existence of multiple subsets of neurons responding to itch-provoking stimuli is supported by recent reports that histamine-and cowhage-induced itch involve different sensory circuits (26)(27)(28)(29). Histamine-induced calcium responses were observed in 23% of IB ϩ and 7% of the IB4 Ϫ neurons (9).…”
mentioning
confidence: 61%
“…Shelley and Arthur (1955) suggested that the active component, although not isolated, was a protease, which they named mucunain. Cowhage has been used recently to investigate sensory modalities and distinguish between histamine and nonhistamine pathways in humans and monkeys (Johanek et al, 2005(Johanek et al, , 2007Davidson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1a) into the superficial skin produces itching. This itching may be accompanied by localized erythema and edema of a few millimeters but a flare or wheal does not occur (Johanek et al, 2007). The response to the active component is not considered allergic, because pruritus is noted after first exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Johanek et al 31 compared skin reaction to histamine, with skin reaction to cowhage spicules. 5,13 The cowhage spicules produced less vasodilation.…”
Section: 1322mentioning
confidence: 99%
“…Additionally, topical capsaicin eliminated cowhage-induced itch but not histamine-induced itch, implicating a separate group of itch-sensitive neurons. 5,13,31 Andrew and Craig 32 used histamine on the lumbosacral spinal cords of 33 anesthetized cats to categorize neurons into functional categories. They were able to demonstrate a functionally unique subset of histamine-selective lamina I SST neurons in the cats, which match the response of human neurons to the itch sensation.…”
Section: 1322mentioning
confidence: 99%